Evaluating the applicability and interpretation of digital marketing metrics : A critical comparative study across organic social media, paid social media advertising and email marketing channels - Ahokas, Kim (My University, 2026)
The purpose of this study is to examine how key digital marketing performance metrics differ in their applicability and interpretation across different marketing channels. The study compares four metrics: reach, impressions, engagement rate, and conversion rate. These metrics are examined across three channels: organic social media, paid social media advertising, and email marketing. The study is conducted as a critical and comparative literature-based study. No primary empirical data is collected instead, the analysis is based on previous academic literature. The metrics are evaluated using a context-dependent evaluation framework, which examines the purpose of each metric, its suitability for different channels, its limitations, potential forms of misuse, and the type of decision-making it encourages. The key finding is that digital marketing metrics should not be interpreted separately from campaign objectives, the customer journey, or the channel in which the metric is used. Reach and impressions function best as visibility metrics, especially in organic and paid social media, but they do not in themselves indicate interaction or conversion. Engagement rate is particularly suitable for social media channels, where visible user interaction is central. Conversion rate, in turn, works best in paid social media advertising and email marketing. The study concludes that metric selection should be context-dependent. Marketers should evaluate metrics in relation to the operating logic of the channel, the campaign objective, and the customer journey. Metrics should not be used merely as reporting figures, but as tools for decision-making whose interpretation requires a critical understanding of their limitations.

Tämän tutkimuksen tarkoituksena on tarkastella, miten keskeiset digitaalisen markkinoinnin suorituskykymittarit eroavat sovellettavuudeltaan ja tulkinnaltaan eri markkinointikanavissa. Tutkielmassa vertaillaan neljää mittaria: tavoittavuutta, näyttökertoja, sitoutumisastetta ja konversioastetta. Näitä tarkastellaan kolmessa kanavassa: orgaanisessa sosiaalisessa mediassa, maksetussa sosiaalisen median mainonnassa ja sähköpostimarkkinoinnissa. Tutkielma toteutetaan kriittisenä ja vertailevana kirjallisuuteen perustuvana tutkimuksena. Työssä ei kerätä omaa empiiristä aineistoa, vaan analyysi perustuu aiempaan akateemiseen kirjallisuuteen. Mittareita arvioidaan kontekstisidonnaisen arviointikehyksen avulla, jossa tarkastellaan mittarin tarkoitusta, soveltuvuutta kanaviin, rajoitteita, mahdollisia väärinkäyttötapoja ja sen ohjaamaa päätöksentekoa. Keskeinen tulos on, että digitaalisen markkinoinnin mittareita ei tulisi tulkita irrallaan kampanjan tavoitteista, asiakaspolusta sekä siitä kanavasta, jossa mittaria käytetään. Tavoittavuus ja näyttökerrat toimivat parhaiten näkyvyyttä kuvaavina mittareina erityisesti orgaanisessa ja maksetussa sosiaalisessa mediassa, mutta ne eivät itsessään osoita vuorovaikutusta tai konversiota. Sitoutumisaste soveltuu erityisesti sosiaalisen median kanaviin, joissa käyttäjien näkyvä vuorovaikutus on keskeistä. Konversioaste puolestaan toimii parhaiten maksetussa sosiaalisen median mainonnassa ja sähköpostimarkkinoinnissa. Tutkielman johtopäätöksenä esitetään, että mittarivalinnan tulisi olla kontekstisidonnaista. Markkinoijien tulisi arvioida mittareita suhteessa kanavan toimintalogiikkaan, kampanjan tavoitteeseen ja asiakaspolkuun. Mittareita ei tulisi käyttää pelkkinä raportointilukuina vaan päätöksenteon välineinä, joiden tulkinta edellyttää kriittistä ymmärrystä niiden rajoitteista.
Keywords: marketing; marketing communication; digital marketing; marketing channels; marketing research; social media; advertising; fi=Markkinointi|en=Marketing|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|; Markkinointi